Discovery of Novel HPK1 Inhibitors Through Structure-Based Virtual Screening - Ge, Huizhen; Peng, Lizeng; Sun, Zhou; Liu, Huanxiang; Shen, Yulin; Yao, Xiaojun (Frontiers in Pharmacology, 2022)
Hematopoietic progenitor kinase (HPK1) is a negative regulator of T-cell receptor and B-cell signaling, which has been recognized as a novel antitumor target for immunotherapy. In this work, Glide docking-based virtual screening and kinase inhibition assay were performed to identify novel HPK1 inhibitors. The kinase inhibition assay results demonstrated five compounds with IC50 values below 20 μM, and the most potent one (compound M074-2865) had an IC50 value of 2.93 ± 0.09 μM. Molecular dynamics (MD) simulations were performed to delve into the interaction of sunitinib and the identified compound M074-2865 with the kinase domain of HPK1. The five compounds identified in this work could be considered promising hit compounds for further development of HPK1 inhibitors for immunotherapy.